Memória e história da advocacia assisense (1960 -1989) - David, Priscila [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
During the second half of the twentieth century the law has undergone a process of change in their professional profile. National matters that directly reflected in culture, economy and politics of Brazilian society emerged new paradigms for this category. However, their political and social roots remained touched, being perceived in the deprivation of rights occasioned process during the military dictatorship, the interference and the participation of lawyers within the category of the choices that directed the history of cities - in our case, of the Assis city in São Paulo state. These new subjects were essential in defining urban development because of their active participation in politics and also in the scenario occupied by social elites of power and representation spaces. In this case the law should be understood as one of the defining categories of management of a society. Given this situation, this thesis addressed the perceived changes in the category of lawyers during the years 1960-1989, as well as political and social influence that allowed the construction of their power networks. Furthermore, we discuss the representations about Assis advocacy and social spaces frequented by them. The set of analysis showed important questions about the group and the society of the proposed period

No decorrer da segunda metade do século XX a advocacia passou por um processo de alteração do perfil de seus profissionais. Questões de âmbito nacional que refletiram diretamente na cultura, na economia e na política da sociedade brasileira fizeram insurgir novos paradigmas para essa categoria. Entretanto, suas raízes políticas e sociais permaneceram afloradas, de forma a perceber-se, no processo de privação dos direitos ocasionado durante a ditadura militar, a interferência e a participação de parte da categoria dos advogados nas escolhas que direcionaram a história das cidades - no nosso caso, da cidade de Assis/SP. Esses novos sujeitos foram essenciais na definição do desenvolvimento urbano, em virtude de sua participação ativa na política e, também, nos espaços ocupados pelas elites sociais de poder e representatividade. Nesse caso, a advocacia deve ser compreendida como uma das categorias definidoras da gestão de uma sociedade. Diante dessa conjuntura, a presente tese abordou as alterações percebidas na categoria dos advogados no período de 1960 a 1989, bem como a influência política e social que permitiu a construção de suas redes de poder. Abordo, ainda, as representações sobre a advocacia assisense e os espaços de sociabilidade por eles frequentados. O conjunto da análise permitiu compreender importantes questões sobre o grupo e a sociedade do recorte proposto
Keywords: Representações sociais; Sociologia política; Direito - Historia - Assis (SP); Political sociology